2009
DOI: 10.1002/jbm.b.31544
|View full text |Cite
|
Sign up to set email alerts
|

Macro‐alignment of electrospun fibers for vascular tissue engineering

Abstract: Design of polymeric scaffolds with specific physical and biological properties is a key objective of tissue engineering research. Electrospinning generates loosely connected 3D porous mats simulating extra cellular matrix structure and therefore makes itself an excellent candidate for application in tissue engineering. Besides a high voltage generator and syringe pump, our electrospinning system was improved to add a programmable central controller which monitors system operation. The nozzles connected with sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
64
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(67 citation statements)
references
References 33 publications
(35 reference statements)
2
64
0
Order By: Relevance
“…2 In addition, electrospinning produces nanoarchitecturely patterned fibers in random or aligned form and it has been demonstrated to greatly influence the cell orientation and function, especially in nerve and muscle TE. [3][4][5][6][7] Electrospun aligned nanofibers could also provide better orientation of cardiac cells and might serve as potential scaffolds for cardiac reconstruction. Chemical composition of a scaffold might also be crucial cues, as it affects protein adhesion and distribution, and further influences the cell orientation and positioning.…”
Section: Introductionmentioning
confidence: 99%
“…2 In addition, electrospinning produces nanoarchitecturely patterned fibers in random or aligned form and it has been demonstrated to greatly influence the cell orientation and function, especially in nerve and muscle TE. [3][4][5][6][7] Electrospun aligned nanofibers could also provide better orientation of cardiac cells and might serve as potential scaffolds for cardiac reconstruction. Chemical composition of a scaffold might also be crucial cues, as it affects protein adhesion and distribution, and further influences the cell orientation and positioning.…”
Section: Introductionmentioning
confidence: 99%
“…Groups interested in vascular graft engineering have found that aligned electrospun fibres can influence vascular cell phenotypes as well. Zhu et al report that fibrin-coated aligned PCL fibres enhanced vascular endothelial cell adhesion and von Willebrand factor production over cells grown on polystyrene plates (figure 3a,b; Zhu et al 2010). In a similar illustration of the effects of aligned electrospun fibres, Huijun and colleagues demonstrated that superaligned poly-L-lactic acid fibres could promote peripheral blood endothelial cell proliferation and specify cell orientation.…”
Section: Electrospinningmentioning
confidence: 95%
“…The scaffolds are porous and have fibers that can be tailored to affect cell differentiation, proliferation, and migration [34][35][36][37][38]. These characteristics make electrospun constructs ideal for wound dressings [39,40] and grafts for various tissues such as skin [32,[41][42][43][44][45][46], nerves [32,33,[47][48][49][50][51], vasculature [32,33,41,[51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66], muscle [33,51,67,68], bone [15,32,33,41,51,[69]…”
Section: Electrospinningmentioning
confidence: 99%